SOSIALISASI PRODI D3 TEKNIK MESIN PENGENALAN PROGRAM ZW3D DAN CNC SERTAAPLIKASINYA PADA RANCANG BANGUN MESIN - Alfian; Fardinal; Mulyadi; Ridwan; Junaidi (LPPM ITB AAS Indonesia Surakarta, 2026)
The rapid development of manufacturing industry technology requires vocational education institutions to continuously adapt to industrial needs, particularly in the fields of Computer Aided Design (CAD), Computer Aided Manufacturing (CAM), and Computer Numerical Control (CNC). However, vocational high school students still face limitations in understanding the integrated workflow of mechanical design and manufacturing based on digital technology. This community service activity aimed to socialize the D3 Mechanical Engineering Study Program of Politeknik Negeri Padang and to introduce ZW3D software and CNC technology along with their applications in mechanical design and manufacturing to students of SMK Negeri 1 Padang. The implementation method consisted of preparation, socialization and introduction sessions, interactive discussions, and evaluation through feedback from participants.The activities included presentations on vocational higher education opportunities,demonstrations of ZW3D as an integrated CAD/CAM tool, basic CNC concepts,and an overview ofhydraulic and pneumatic systems used in industrial machinery. The results showed a positive response from students and teachers, reflected in increased understanding of CAD/CAM-CNC concepts, awareness of modern manufacturing technology, and improved motivation to pursue vocational higher education in mechanical engineering. In conclusion, this activity effectively enhanced students'knowledge and readiness to face the demands of modern manufacturing industries and supported the strengthening of linkages between vocational schools and higher education institutions.